Education of Public Understanding of The Importance of Product Brand Registration of Ohoi-Owned Business Entity Partner Business Groups - Labetubun, Muchtar Anshary Hamid; Angga, La Ode; Nabila, Syadzwina Hindun; Panjaitan, Wijaya Natalia (AIWADTHU: Jurnal Pengabdian Hukum, 2025)
Introduction: This study examines the effectiveness of educational programs on the importance of trademark registration for partner business groups of Ohoi-Owned Enterprises in Ohoi Rat, Kei Kecil Timur District, Southeast Maluku Regency.Purposes of The Devotion: This educational program aims to increase public understanding of intellectual property rights protection, especially in terms of product brand registration. Method of The Devotion: The methods used include counseling, focus group discussions, brand registration simulations, and individual consultations.Results Main Findings of the Devotion: The results of pre- and post-education surveys show a significant increase in public understanding of the benefits and procedures of brand registration.  As many as 75% of respondents understand the importance of brand registration after the program, an increase of 60% from before.  Several obstacles were identified, such as high registration fees and complex procedures.  Policy recommendations include providing incentives, simplifying procedures, and improving access to information.  This program is expected to contribute to the improvement of the village economy through Brand protection for Micro and Small Enterprises.